2022
DOI: 10.1021/acs.jpcc.2c03845
|View full text |Cite
|
Sign up to set email alerts
|

Does an Ionomer Penetrate a Carbon Mesopore? Free-Energy Analysis Using Molecular Dynamics Simulations

Abstract: Mesoporous carbon support enhances the catalytic activity and gas diffusivity of the cathode catalyst layers of polymer-electrolyte fuel cells. The key role of the mesopores is believed to be their suppression of catalyst poisoning by the ionomers and reduction of the oxygen diffusivity near the catalysts. However, because of the difficulty to observe the ionomer distributions directly, it is unclear whether the ionomer penetrates the mesopores. Here, using molecular dynamics simulations of ionomer penetration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…The five-walled CNTs were generated using d and h obtained from n a and n b by the cylindrical projection of a graphene sheet of length πd and height h according to a previous study. 47 Finally, a periodic boundary of length h was applied in the direction of the tube axis, and the desired periodic infinite CNT system was obtained. The thickness of the five-layered graphite is approximately 1.7 nm.…”
Section: ■ Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The five-walled CNTs were generated using d and h obtained from n a and n b by the cylindrical projection of a graphene sheet of length πd and height h according to a previous study. 47 Finally, a periodic boundary of length h was applied in the direction of the tube axis, and the desired periodic infinite CNT system was obtained. The thickness of the five-layered graphite is approximately 1.7 nm.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Then, for input pore diameter d 0 and cylinder length h 0 , we can estimate n a and n b as n a = ceil true( π ( normald 0 + 2 normald CC inter n layer ) 3 d CC intra true) and goodbreak0em1em⁣ n b = ceil ( h 0 3 normald cc intra ) where ceil( x ) is a rounded-up value of x ; d CC inter = 0.335 nm is the interlayer distance between CNT walls; n layer = 0,1,2,3,4 are the indexes of the CNT layers. The five-walled CNTs were generated using d and h obtained from n a and n b by the cylindrical projection of a graphene sheet of length π d and height h according to a previous study . Finally, a periodic boundary of length h was applied in the direction of the tube axis, and the desired periodic infinite CNT system was obtained.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transmission electron microscopy observations indicated that a large portion of the Pt nanoparticles are located in the pores of the porous carbon particles [53]. Electrochemical measurements [37] and MD simulations [54] indicated that these Pt particles are not covered by ionomers because the ionomer molecules do not easily penetrate the pores. In addition, protons can access the Pt nanoparticles in the pore through liquid water without an ionomer [55].…”
Section: Strategies For Mitigating Ionomer Adsorptionmentioning
confidence: 99%